Association of counselling with breastfeeding technique: a study from rural area of southern Haryana - Rana, Vandana; Aggarwal, Sonam (International Journal Of Community Medicine And Public Health, 2022)
Background: Correct breastfeeding technique (BFT) has been shown to be important to establish breastfeeding, to ensure milk transfer and to prevent breastfeeding problems. Counselling is seen as an important pathway to address the problem of inappropriate BFT. This study was conducted to assess breastfeeding technique and its association with counselling. Methods: The study was community based cross sectional study. After taking permission from institutional ethical committee a cross-sectional study was undertaken among the mothers of children (0 to 23 months). A total of 360 mothers were interviewed and observed with the help of semi-structured interview schedule based on WHO breastfeeding observation checklist after taking written informed consent. Descriptive statistics were used to summarize all variables of interest in the study population. The data were analysed using Epi-Info. Results: Out of 360 mothers, only 1/5th of the mothers (21.4%) were found to be currently not practicing breastfeeding, 78.6% were doing breastfeeding, in 18.9% correct breastfeeding technique and in 59.7% incorrect breastfeeding technique was seen. ANC counselling significantly improves breastfeeding technique (p=0.000). PNC counselling was found to be significantly improving the current breastfeeding status (p=0.011). Conclusions: In the study area the proportion of ineffective breastfeeding was very high and was significantly associated with not receiving counselling during ANC and PNC.